Cultural Theory and History: Innovation and Subjectivity - Kamińska, Magdalena; Urban, Olga (Wydawnictwo Naukowe Wydziału Nauk Społecznych WUniwersytetu im. Adama Mickiewicza w Poznaniu, 2014)
The book, divided into two chapters, is dedicated to the theme of social, historical and cultural change. Magdalena Kamińska focuses her attention on the relationship between technological innovation and socio-cultural change. Particularly, she discusses the cultural contexts and social conditions under which the innovation is able to cause the change. The chapter is based on the examples taken from media history. Olga Urban, then, concentrates on the role of the individual within the social and cultural processes of change. She focuses on the problem of human subjectivity, and analyzes different ways of conceptualizing these issues in selected fields of humanities and social sciences.
Keywords: theory of culture; archeology of media; innovation, cultural change; rationality; subjectivity; participation in culture; cultural history